Health status and health-seeking behaviour between interprovincial and intraprovincial rural-to-urban young migrants in Nanjing, China - Liying Zhang; Xiaoming Li; Hongmei Yang; Rong Mao; Qun Zhao (Asia-Pacific Population Journal, 2013)
There has been a dramatic increase in interprovincial migration in China because of regional economic disparities. Interprovincial migration has contributed to population redistribution and economic development, however, limited data are available to examine whether the health status of interprovincial migrants differs from that of intraprovincial migrants. Data from 1,842 rural-to-urban temporary migrants aged 18-30 years were analyzed to examine the differences in health status (measured by self-rated health, physical problems, depression), and health-seeking behaviour between these two types of internal migrants. It was found that interprovincial migrants were more likely to report depression symptoms and were less likely to seek formal health-care services than intraprovincial migrants. The findings indicate that specific attention should be given to health promotion and health-care access of interprovincial rural-to-urban migrants.